(3GdEjVGM TQM GdeaUds - (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS GdeGdcj GdcQOj GdCSfGFj GdeUQj , CHh YeQh LeGd GdOjf GHf GdMGLH , J (B646 (3g` s; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3GHf fUQ GdcGJH s)
(3ChdgG (B:s
(3Gddg CMeO Ydi WQjbI EjGc fYHO JbOjekG ddCge heG jfbd Cfg ddMUQ dG Odjd Ydjg s
(3BNQgG (B:s
(3bGd(B: (3hEPG cGfhG eef jMPahf cQghG GLJeGY GdeKdjf eY EecGf JNajag ef MQha GdJNaja Chdi GdGSJOdGd HGYJHGQ TPhPjgeG hGddg CYde s
(3GdfSNI HgG MhGTs
(3GfXQ GdLRA GdChd Qbe (B29(3, (B30 (3fMh s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs